Atypical presentation of moyamoya disease in an infant with a de novo RNF213 variant. (21st July 2015) - Harel, Tamar; Posey, Jennifer E.; Graham, Brett H.; Walkiewicz, Magdalena; Yang, Yaping; Lalani, Seema R.; Belmont, John W.
<x xml:space="preserve">Abstract</x> Variants in RNF213 lead to susceptibility to moyamoya disease, a rare cerebral angiopathy characterized by bilateral stenosis of the internal carotid arteries and development of a compensatory collateral network. We describe a 3‐month‐old female with seizures, arterial narrowing involving the internal carotid and intracranial arteries and inferior abdominal aorta, and persistently elevated transaminases. Whole exome sequencing demonstrated a novel de novo variant in RNF213, securing a molecular diagnosis and directing appropriate intervention. This report underscores the role of whole exome sequencing in cases for which a complex and atypical presentation may mask diagnosis. Furthermore, the early and severe presentation in our patient, in conjunction with a novel de novo RNF213 variant, suggests that specific variants in RNF213 may lead to a Mendelian form of disease rather than simply conferring susceptibility to multifactorial disease. © 2015 Wiley Periodicals, Inc.